1994
DOI: 10.2307/3432234
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding to Crystalline Silica Characterized by Fourier-Transform Infrared Spectroscopy

Abstract: The interaction of DNA with crystalline silica in buffered aqueous solutions at physiologic pH has been investigated by Fourier-transform infrared spectroscopy (FT-IR). In aqueous buffer, significant changes occur in the spectra of DNA and silica upon coincubation, suggesting that a DNA-silica complex forms as silica interacts with DNA. As compared to the spectrum of silica alone, the changes in the FT-IR spectrum of silica in the DNA-silica complex are consistent with an Si-O bond perturbation on the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 34 publications
4
40
0
Order By: Relevance
“…Previous IR and Raman spectroscopic studies have shown that phosphoryl groups of a DNA backbones are the main functional groups in the DNA sticking to silica (Mao et al, 1994;Mercier and Savoie, 1997). This is consistent with our results that phosphates form stronger Hbonds with neutral silanols ("SiOH) than other functional groups of polymers:…”
Section: Discussionsupporting
confidence: 93%
“…Previous IR and Raman spectroscopic studies have shown that phosphoryl groups of a DNA backbones are the main functional groups in the DNA sticking to silica (Mao et al, 1994;Mercier and Savoie, 1997). This is consistent with our results that phosphates form stronger Hbonds with neutral silanols ("SiOH) than other functional groups of polymers:…”
Section: Discussionsupporting
confidence: 93%
“…26 Mao and co-workers studied DNA binding to silica by Fourier-transform infrared spectroscopy. 96 We conclude with perhaps a provocative statement. Much has been written about the uniqueness of the water-biomolecule interface.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 84%
“…Its adsorption by silica was extensively investigated. [17][18][19] It is reported that silanol group through the surface enhance the interaction.…”
Section: Introductionmentioning
confidence: 99%